Platelet Derived Vesicles Enhance the TGF-beta Signaling Pathway of M1 Macrophage - Song, Nan; Pan, Kaifeng; Chen, Lei; Jin, Keke (Frontiers in Endocrinology, 2022)
Macrophages, mainly divided into M1 pro-inflammatory and M2 anti-inflammatory types, play a key role in the transition from inflammation to repair after trauma. In chronic inflammation, such as diabetes and complex bone injury, or the process of certain inflammatory specific emergencies, the ratio of M1/M2 cell populations is imbalanced so that M1 macrophages cannot be converted into M2 macrophages in time, resulting in delayed trauma repair. Early and timely transformation of macrophages from the pro-inflammatory M1 type into the pro-reparative M2 type is an effective strategy to guide trauma repair and establish the original homeostasis. We prepared purified nano-platelet vesicles (NPVs) and assessed their effects on macrophage phenotype switching through transcriptome analysis. The results show that NPVs promote pathways related to angiogenesis, collagen synthesis, cell adhesion, and migration in macrophages, and we speculate that these advantages may promote healing in traumatic diseases.